A rare variant of thalamic stroke- artery of Percheron infarct - R., Shreenidhi; Sivasamy, Manoj; M. K., Nishaanth; Kumar, Sathish; Karthik S., Prasanna (International Journal of Advances in Medicine, 2023)
The thalamus is a walnut-sized structure that is located in the brain which receives rich blood supply from posterior cerebral artery and its communicating branches. One of the unusual presentations is the infarction of artery of percheron. Hereby reporting a case of 68-year-old female with no known co-morbidities who presented to the emergency department with complaints of sudden onset loss of consciousness in the morning. On further investigation, was found to have infarction of one of the variants of thalamic perforating arteries.